Cultural Factors Associated With Criminal Male Behavior And Inmate Population - Martinez-Lanz, Patricia; Sánchez-Guerrero, Alejandro; Hernández-Valdez, Martha Patricia (Advances in Social Sciences Research Journal, 2020)
Over the last decade, crime has reached unprecedented levels causing violent death in Mexico. To establish factors that potentially can facilitate crime, as well as the status of emotional wellbeing presented in prison population, the present study was realized with a sample composed of 299 inmates of the Federal Center for Social Reinsertion in Oaxaca, Mexico. The questionnaire was specifically developed, designed and applied to evaluate this population, analyzing sociodemographic factors and four Likert scales: substance consumption (drugs and alcohol), domestic violence and depressive symptoms. Reliability was adequate (Cronbach's Alpha= .703) and the instrument validity showed appropriate relations between the reagents of each scale. Results showed -through Chi Square analysis- statistically significant differences in the correlations between sociodemographic factors, domestic violence, addictions and depressive symptoms. Results reported that most of inmates were between 28 and 47 years old (51.8%), with a low educational level (elementary school 42.5%), in consensual union (42.5%), high and severe levels of alcohol consumption (43.5% of the cases) and reported presence of high and severe level of depression (28.9% of the cases). The results are part of a national study of all Federal Centers for Social Reinsertion System in Mexico, in order to developed intervention strategies used in prison to prevent crime.